VAI TRÒ CỦA THANH TRA TỈNH TRONG CÔNG TÁC GIẢI QUYẾT KHIẾU NẠI, TỐ CÁO TẠI TỈNH LÂM ĐỒNG HIỆN NAY - Nguyễn, Thị Oanh (2023)
https://thanhnienviet.vn/2023/07/04/vai-tro-cua-thanh-tra-tinh-trong-cong-tac-giai-quyet-khieu-nai-to-cao-tai-tinh-lam-dong-hien-nay/